Influence of physicochemical properties of the gram-negative bacteria cell surface on the resistance to streptomycin - A. B. Pshenichnikova; E. S. Gavrilova; V. I. Shvets (Тонкие химические технологии, 2011)
The surface electrokinetic and potentiometric acid-base properties of whole cells of the gram-negative bacteria - natural sensitive strain and mutant streptomycin-resistant strain of the obligate methylotrophic bacterium Methylophilus quaylei (M. quaylei MT and M. quaylei SM+) and of heterotrophic bacterium Stenotrophomonas maltophilia - in standard growth conditions and in the presence of oleic acid were studied. An ability of oleic acid to accelerate bacterial growth and adaptation of methylotrophic bacteria to the antibiotic stress was discovered. A mechanism of resistance to streptomycin is discussed.